An experimental and numerical study on the effectiveness of automotive vortex generators - Kumar, Pasupuleti Pavan (Nanyang Technological University, 2021)
This study investigated the effectiveness of 4 distinct vortex generators (VGs) (Wishbone, Rocket, Simple, Jagged) of different shapes, sizes and heights that were found in the commercial automotive market at conventional road limit speeds. The flow separation control through these VGs was studied with the help of surface oil flow visualizations and CFD simulations. These methods were used to best visualize the shape of the vortex wake, the wake roll-up and the resulting flow signatures for all 4 distinct VGs. The investigation tested the VGs at two different orientations – non-skewed and at skewed angles of 30° to the freestream direction. The combined effect of multiple VGs in an array configuration was also tested for these two orientations. The Wishbone VG in particular clearly showed a structured vortex at its rear in both skewed and non-skewed orientations. The development of the vortices emanating from it persisted strongly downstream in both orientations. High flow blockage encountered by the Wishbone VG in the 0° orientation as well as the other VGs that were skewed, produced qualitatively stronger and larger streamwise vortices. Whereas, smaller flow blockage by the smaller VGs (Rocket, Simple and Jagged) in the 0° orientation produced only weak streamwise vortices. Both the experimental and computational results proved that the Rocket, Simple and Jagged VGs were not as effective as the Wishbone VG in the 0° orientation as the vortices experienced rapid decay of peak vorticity which were at times not even strong enough to even persist till 100mm upstream of the ramp. The combined effect of an array of smaller VGs skewed 30° caused complex 3D flows with strong mixing between boundary layers. However, the results were clear in demonstrating that the use of multiple Wishbone VGs in the 0° orientation was the most effective method to mitigate flow separation.